2016
DOI: 10.1007/s40093-016-0139-1
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of waste lignin to prepare controlled-slow release urea

Abstract: Purpose The present work reports an economically attractive improvement in the area of producing particulate slow release nitrogen fertilizer using lignin as a waste effluent of pulp and paper manufacturing process. Methods An improved coating of modified lignin was applied on the surfaces of the individual urea particles. The Kraft and Sulfite black liquors obtained from two different paper pulping units and were used as sources of sulfate and sulfite lignin, respectively. Chemical modification of extracted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 33 publications
(30 reference statements)
0
34
0
Order By: Relevance
“…Priamine compare the lower viscosity obtained when THF solvent was used. Therefore, high thickness, compacted and good adhesion between the granule and the coating were obtained by reducing the pores sizes which became smaller as the coating percentage increased (Behin and Sadeghi, 2016) (Fig. 3).…”
Section: Insert Fig4mentioning
confidence: 98%
See 2 more Smart Citations
“…Priamine compare the lower viscosity obtained when THF solvent was used. Therefore, high thickness, compacted and good adhesion between the granule and the coating were obtained by reducing the pores sizes which became smaller as the coating percentage increased (Behin and Sadeghi, 2016) (Fig. 3).…”
Section: Insert Fig4mentioning
confidence: 98%
“…Indeed, its low viscosity conferred to the shell coatings a compact structure and covered all the cavities and cracks in the surface of the uncoated DAP fertilizers when the percentage of coating increased leading to a smooth surface (Fig 3f). With its good water repellency, hydrophobic nature, Priamine brings excellent barrier properties and thus moderated the P release rate (Behin and Sadeghi, 2016).…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of controlled release is regulated first by the progressive degradation of the coating and second by the osmotic pressure inside the core; thereafter, high hydrophilic and environmentally green compounds must be considered to avoid the pollution of soil after coating degradation. In this sense, the more recent research is dedicated to the study of coating or matrix-based on natural materials, such as bentonite and cotton stalks, 11 lignin, 12 wheat straw, 13 chitosan and vegetal cellulose, 14 and chitosan and potato starch. 15 Studies so far demonstrated that the obtainment of a gradual controlled release over a period of 21 days is difficult because it is necessary to avoid too fast biodegradation of the coating due to very high hydrosolubility of the natural materials, and therefore, research must be focused on the need for greater control of the coating formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research efforts have been aimed at developing suitable mitigation strategies to reduce gaseous and leaching losses of N from intensively managed agricultural systems 7 10 . Mitigation strategies, such as using controlled release or enhanced efficiency fertilizers or combined application of organic and inorganic fertilizers to minimize the loss of N for improving its use efficiency by crops have been extensively studied in the last few decades 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%